Paper from cotton wastes - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
A small plant to manufacture paper and cardboard from cotton twigs was recently established in Bamako, Mali. Over 50 t of boxes and shirt cartons are scheduled to be produced during the next year. This enterprise is one of the results of studies...